Chapter L'Epistola Alexandri Magni ad Aristotelem nello Zibaldone Laurenziano, Plut. XXIX 8 - Zanobi, Marina (Studi e saggi, 2021)
This essay considers the Epistola Alexandri Magni ad Aristotelem de miraculis Indiae copied by Giovanni Boccaccio in the ''Zibaldone Laurenziano'', the autograph anthology held in the Medicean-Laurentian Library in Florence (ms. Plut. XXIX 8). The purpose of this article is to demostrate that the text of the Epistola copied by Boccaccio derives from the tradition of Godfrey of Viterbo's Pantheon. The paper also offer an interpretative transcription of the text followed by an apparat of notes